How COVID-19 pandemic lockdown has affected sports practice - Mazza, B. (Italian Sociological Review, 2021)
The recent pandemic generated by COVID-19 has changed how sports are habitually practised, necessitating a form of at-home sport to enable practitioners to continue exercising and training. This also touches upon how sports are `delivered`, with home-based consumers having control over the times, ways and spaces given to sport, as transmitted by digital means. During lockdown, opportunities to take advantage of apps and content and/or follow online lessons on social networks notably intensified. These changes in sports practice generate a series of research objectives, to determine: how digital media has created a new environment for socializing and sports practice; how digital devices are used to play home sports; and which players encourage people to exercise at home. With these objectives in mind, a two-phase research was launched at the SapienzaSport centre. The first questioned a group of about 600 practitioners, with a relatively high cultural and socioeconomic level along with access to digital opportunities, to investigate their sports habits during lockdown. The goal was to focus on those not negatively affected by the digital divide. The second phase aimed at studying the subsequent implications, starting from September 2020 (when sports-related activities resumed in Italy), while understanding whether and in what way doing physical activity had changed. In this paper we report and analyse the main results.